Clinicopathological Analysis of Postmenopausal Bleeding and Endometrium - Hota, Basanta Manjari; Bakshi, Kavitha; Lokam, Geetha; Movva, Naimisha (Folia Medica Indonesiana, 2024)
Highlights: 1. Malignancies in postmenopausal bleeding are not very common, yet it is necessary to evaluate the etiology and implement appropriate treatment strategies. 2. The findings of this study highlight the need for early detection of benign, premalignant, or malignant cases to provide more effective management, prevent the development of cancer, and improve the prognosis of the condition. Abstract Bleeding from the genital organ after a year of menopause is called postmenopausal bleeding. The causes may be either benign or malignant, originating from genital (uterine or extrauterine) and extragenital sites. About 3% of postmenopausal women suffer from uterine cancer. This present study aimed to analyze the clinical significance of postmenopausal bleeding concerning the source, associated risk factors, and various endometrial pathologies, including malignant and premalignant conditions. This retrospective study was conducted over four years and featured postmenopausal bleeding patients who met the inclusion criteria. Different causes of bleeding were noted and managed. Data collection on the history, clinical examination, blood test, and endometrial biopsy was performed on women with endometrial bleeding. The collected data were analyzed using standard descriptive statistics and presented using frequency tables. A total of 88 women were admitted, of whom 73 (82.95%) had endometrial bleeding and 15 (17.05%) experienced bleeding from other sites. The endometrial bleeding group mostly consisted of women aged >50–60 years (45.20%). Hypertension (26.03%), diabetes (21.91%), obesity (43.83%), and nulliparous (5.48%) were the risk factors present among the patients. The majority of the patients (41.10%) were within five years of menopause. The transvaginal ultrasound findings indicated that 56.16% of the women had an endometrial thickness of >10 mm, while 9.59% had an endometrial thickness of â‰¤4 mm. Upon histological investigation, endometrial hyperplasia (34.24%), atrophy (38.36%), and cancer (4.11%) were detected. Furthermore, a prevalence of 16.44% was identified as proliferative endometrium, whereas polyps were found in 6.84% of cases. In conclusion, postmenopausal bleeding is mostly benign, but it may raise concerns about the possibility of malignancy, which can be distressing for women. Disregarding the amount and frequency, postmenopausal bleeding requires a thorough evaluation, primarily because adequate management can prevent the progression of many premalignant cases to be endometrial cancer.